Employing Peter Newmark's Approaches to Language Transfer to Study English -Vietnamese Translation of Metaphors and Similes - Nguyễn Thị Nguyệt (2008)
The seven procedures proposed by Peter Newmark for translating metaphors, and, by expansion, for translating similes have become an almost undisputable theoretical foundation for the translation of this type of figure of speech. However, ….